The Role of Communication in Shaping Local Public Space: A Phenomenological Study of Political Variables in M'sila Province, Algeria - Menouar, imene; yahia, takieddine (Journal of Social Sciences and Humanities, 2025)
This phenomenological study investigates the evolution of the local public sphere in M'sila, Algeria, tracing its shift from historical cultural-literary dominance towards contemporary political and social discourse. Employing participant observation grounded in philosophical phenomenology, the research critically examines the role of traditional and modern media in shaping public opinion within this context. Key findings indicate significant challenges to equitable participation, particularly for women and marginalised groups, hindering the formation of inclusive public opinion. Furthermore, recent Algerian political shifts have precipitated an amplified political discourse and proliferation of rumours, collectively contributing to the destabilisation of the public sphere's integrity and function. The study concludes with practical recommendations aimed at fostering constructive community dialogue and activating meaningful participation across societal groups, essential for enhancing the democratic resilience and representativeness of M'sila's public sphere.